Understanding the approaches for accommodating multiple stakeholders' interests - Ramírez, R. (2001)
Conflict and collaboration are often treated as mutually exclusive modes of stakeholder interaction, with little understanding of the contexts in which stakeholder relationships take place. The conceptual framework in this paper addresses accommodating multiple interests as an evolving, cyclical, iterative process, swinging back and forth from collaborative to conflictive situations. A typology is presented with nine contextual facets that come into play in accommodating multiple interests: the nature of the problem, the stakeholders, the convenor, the networks, stakeholders' capacities, stakeholders' choices over procedures to deal with conflict, negotiation, and dispute resolution. The nine facets function as lenses through which to analyse multiple stakeholder situations. The typology is used to analyse four existing approaches: Collaborative Management, Collaborative Learning, Rapid Appraisal of Agricultural Knowledge Systems (RAAKS) and 'linked local learning'. A set of criteria to assess their impact is developed, and desirable future directions for methodological development are discussed.